Characterization of polyphenol oxidase from Cape gooseberry (Physalis peruviana L.) fruit. (15th April 2016) - Bravo, Karent; Osorio, Edison
Highlights: Biochemical properties of PPO from Cape gooseberry were analyzed. The optimal pH and temperature for three substrates were determined. The Cape gooseberry PPO activity decreased over time with fruit ripening. Different substrates were analyzed to determine their affinities with PPO. PPO activity was strongly inactivated by quercetin and ascorbic acid. Abstract: Cape gooseberry ( Physalis peruviana ) is an exotic fruit highly valued, however it is a very rich source of polyphenol oxidase (PPO). In this study, Cape gooseberry PPO was isolated and biochemically characterized. The enzyme was extracted and purified using acetone and aqueous two-phase systems. The data indicated that PPO had the highest substrate affinity for chlorogenic acid, 4-methylcatechol and catechol. Chlorogenic acid was the most suitable substrate ( Km = 0.56 ± 0.07 mM and V max = 53.15 ± 2.03 UPPO mL −1 min −1 ). The optimal pH values were 5.5 for catechol and 4-methylcatechol and 5.0 for chlorogenic acid. Optimal temperatures were 40 °C for catechol, 25 °C for 4-methylcatechol and 20 °C for chlorogenic acid. In inhibition tests, the most potent inhibitor was found to be ascorbic acid followed byl -cysteine and quercetin. This study shows possible treatments that can be implemented during the processing of Cape gooseberry fruits to prevent browning.